Genetic research and consent: On the crossroads of human and data research. (2nd August 2018) - Pormeister, Kärt
Abstract: This paper explores the legal and ethical concept of human subject research in order to determine whether genetic research with already available biosamples and data falls within this concept. Although the ethical concept seems to have evolved to recognize research based on data as human research, from a supranational legal perspective this form of research is not considered human subject research. Thus human subject research regulations do not apply and therefore do not invoke the requirement of obtaining consent prior to using an individual's biosample or genetic data in research. Furthermore, it remains ambiguous in both the legal and ethical realm whether the use of biosamples or genetic data without additional links to the individual would invoke the same safeguards as research involving additional or specific identifiers. Seeing that research based on already available biosamples and genetic data is not governed by rules concerning human subject research, the second part of the paper analyses whether any consent requirements apply for the further use of already available bio‐samples or genetic data in research. Whereas further use of biosamples is subject to considerably lax consent requirements under Article 22 of the Oviedo Convention, under the General Data Protection Regulation further use of genetic data might not be subject to a prior consent requirement at all, unless it is stipulated in national laws. When it comes to clinical trials, however, sponsors will have the possibility under Article 28(2) of Regulation 536/2014 to obtain open consent for further use of data in any kind of future research.